Rapid acting fentanyl formulations in breakthrough pain in cancer: drug selection by means of the System of Objectified Judgement Analysis - Janknegt, Robert; van den Beuken, Marieke; Schiere, Sjouke; Überall, Michael; Knaggs, Roger; Hanley, Jaquie; Thronaes, Morten (BMJ Publishing Group, 2017)
Drug selection of rapid acting fentanyl formulations in the treatment of breakthrough pain in patients with cancer is performed by the System of Objectified Judgement Analysis method. All seven available formulations were included in the analysis. The following selection criteria were used: number of available strengths, variability in the rate of absorption, interactions, clinical efficacy, side effects, ease of administration and documentation. No direct double-blind comparative studies between two or more formulations were identified and the clinical documentation of all formulations is limited. The most distinguishing criterion was ease of use. This led to slightly higher scores for Abstral, Instanyl and PecFent than for the other formulations. The pros and cons of each formulation should be discussed with the patient, and the most suitable formulation selected for each individual patient.